Cytokines and Liver Diseases - Herbert Tilg (Canadian Journal of Gastroenterology)
Cytokines are pleiotropic peptides produced by virtually every nucleated cell in the body. In most tissues, including the liver, constitutive production of cytokines is absent or minimal. There is increasing evidence that several cytokines mediate hepatic inflammation, apoptosis and necrosis of liver cells, cholestasis and fibrosis. Interestingly, the same mediators also mediate the regeneration of liver tissue after injury. Among the various cytokines, the proinflammatory cytokine tumour necrosis factor-alpha (TNF-a) has emerged as a key factor in various aspects of liver disease, such as cachexia and/or cholestasis. Thus, antagonism of TNF-a and other injury-related cytokines in liver diseases merits evaluation as a treatment of these diseases. However, because the same cytokines are also necessary for the regeneration of the tissue after the liver has been injured, inhibition of these mediators might impair hepatic recovery. The near future will bring the exiting clinical challenge of testing new anticytokine strategies in various liver diseases.